2020
DOI: 10.1111/jvim.15704
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of systemic inflammatory response syndrome and serum concentrations of acute phase proteins, cholesterol, and total thyroxine in cats with panleukopenia

Abstract: Background Feline parvovirus (FPV) is a common and potentially lethal infectious agent in cats. Objective To assess the prognostic value of age, neuter status, serum concentrations of serum amyloid A (SAA), haptoglobin, cholesterol and total thyroxine (tT4), and the presence of systemic inflammatory response syndrome (SIRS) in cats with panleukopenia. Animals Client‐owned cats with FPV infection diagnosed by a positive fecal ELISA test, positive PCR on feces or blood or both. Methods Retrospective cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 48 publications
4
21
0
1
Order By: Relevance
“…12,16,22,[24][25][26] Few studies have examined the relationship between thyroid function and mortality in cats with NTIS. [27][28][29][30] In 2 studies that examined cats with a variety of nonthyroidal diseases, 27,28 cats that died or were euthanized had lower serum T 4 concentrations than did cats that survived, suggesting that serum T 4 concentrations may also be indicative of survival outcome. Similarly, a recent study of cats with panleukopenia reported that low serum T 4 concentrations were associated with poor outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,16,22,[24][25][26] Few studies have examined the relationship between thyroid function and mortality in cats with NTIS. [27][28][29][30] In 2 studies that examined cats with a variety of nonthyroidal diseases, 27,28 cats that died or were euthanized had lower serum T 4 concentrations than did cats that survived, suggesting that serum T 4 concentrations may also be indicative of survival outcome. Similarly, a recent study of cats with panleukopenia reported that low serum T 4 concentrations were associated with poor outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent study of cats with panleukopenia reported that low serum T 4 concentrations were associated with poor outcome. 30 To our knowledge, no study has evaluated if serum T 3 or TSH concentrations can help predict survival outcome in cats with NTIS.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that, in the present study, the presence of antibodies against FPV in serum samples collected on admission was positively associated with survival, with higher loads on admission in cats that died compared to survivors; similar results have already been described in the literature in cats infected with feline herpesvirus-1, feline calicivirus, and FPV [31]. Considering that one inclusion criterion was that cats were not vaccinated for FPV, the presence of antibodies on admission might suggest a previous contact with the virus or false positives due to nonspecific binding to the test reagents [31]; however, these hypotheses are less probable since the presence of antibodies is a strong predictor of protection against FPV reinfection and subsequent clinical disease, and since the slides for immunofluorescence assays were tested for potentially contaminating other feline viruses [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Because all cats came from a shelter where FPV is endemic, it is more likely that cats with neutralizing antibodies were admitted at a later stage of the infection; in fact, it has been shown that FPV antibodies production starts 8 days post-infection and precedes leukocytes improvement by several days [32].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of subclinical infections remains unknown [2]. Body weight, the severity of clinical signs, thrombocytopenia, hypoalbuminemia, hypokalemia, glucose administration, total T4 have been identified as negative prognostic factors in cats infected by FPV, whereas leukopenia has been inconstantly recognized as a negative outcome predictor [3][4][5]. So far, no specific antiviral therapy against FPV infection has been tested in cats, and its management relies upon supportive treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation